Effects of Epiphytes on the Seagrass Phyllosphere - Brodersen, Kasper Elgetti; Kühl, Michael (Frontiers in Marine Science, 2022)
The seagrass phyllosphere consists of a dynamic mosaic of physico-chemical microgradients that modulate light harvesting, gas and nutrient exchange between the photosynthetic leaves and the surrounding water-column. The phyllosphere is thus of vital importance for seagrass growth and fitness. However, unfavorable environmental conditions such as water-column hypoxia, increasing temperature and high nutrient inputs that are predicted to increase in frequency and severity in the Anthropocene, can render the leaf microenvironment into a hostile microhabitat that is challenging or even harmful for the plants—especially if leaves are covered by epiphytic biofilms. Here we summarize effects of epiphytic biofilms on seagrass leaves and discuss how they change and affect the biogeochemical processes and chemical conditions in the seagrass phyllosphere. During night-time, water-column hypoxia can lead to anoxic conditions at the leaf/epiphyte interface, reducing diffusive O2 supply and thus O2 availability for plant respiration and transport to below-ground tissues. Furthermore, anoxia in epiphytic biofilms can also enable anaerobic microbial processes that can lead to harmful nitric oxide production via denitrification. Such microenvironmental stress conditions at night-time are exacerbated by increasing temperatures. In the light, the leaf epiphytic biofilm community often results in lower leaf photosynthetic activity and efficiency due to epiphyte-induced shading and a combination of O2 build-up and CO2 reduction in the phyllosphere owing to thicker total diffusional pathways, phyllosphere basification and epiphytic carbon fixation. Furthermore, absorbed light energy in the epiphytic biofilm can also drive an increase in the leaf surface temperature relative to the surrounding seawater potentially aggravating heating events in the surrounding seawater. In combination, all these above-mentioned diurnal effects of epiphytes result in higher compensation photon irradiance of epiphyte-covered leaves and thus higher light requirements of seagrasses.